Dynamic analysis of PEM fuel cells and metal hydrides on a zero-emission ship: A model-based approach. (16th September 2021) - Cavo, M.; Gadducci, E.; Rattazzi, D.; Rivarolo, M.; Magistri, L.
Abstract: As the interest in hydrogen and PEM fuel cells is growing, it is crucial to define the best technology for fuel storage, especially in the transportation field. Metal hydrides show different benefits, including the possibility of thermally coupling the hydrogen storage and utilization systems: fuel cells require heat subtraction for ensuring proper operation, while metal hydrides require heat to activate the hydrogen release reactions. This work describes the integration of PEMFCs and metal hydrides on board a zero-emissions ship, with a special focus on their thermal coupling; a model-based approach is developed to ensure the system's feasibility at different load demands for the vessel, including transient conditions. The study is based on the real application of an innovative zero-emissions ship (ZEUS) financed by Fincantieri-Isotta Fraschini S.p.A, where the total power installation is set at 144 kW by PEMFC and 50 kg of hydrogen are stored by metal hydrides. Highlights: Dynamic model of PEMFC and metal hydrides is developed for maritime application. A thermal control system based on PI controller is implemented. Real ship load profiles are analyzed with two system configurations. The feasibility of thermal coupling is verified for both configurations. Hydrogen consumption is minimal for the one branch configuration.